The Importance of Financial Performance for Evaluating Supplier Performance – a Comparison with the Internal Ratings of Credit Institutions - Gunther Meeh-Bunse; Anke Hermeling (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Due to changing procurement policies and procurement markets, suppliers increasingly face evaluation of their holistic supplier performance. In this context, the assessment of financial strength is increasingly emphasized. Hence, (potential) suppliers are required to prove their financial soundness towards the assessing (potential) corporate customer. Traditionally, such evidence was only to be offered to banks that create compulsory internal credit ratings. The goal of this paper is to compare procurement in voluntary supplier performance evaluation, particularly the assessment of financial strength, with the procurement when creating compulsory internal ratings by banks. This should on the one hand identify potential concordances and interdependences while on the other hand improve awareness for suppliers. Presentation and analysisof selected indicator systems assess financial strength within supplier evaluation and within the internal rating by banks. Despite the potential different objectives of banks and (potential) corporate customers apparently significant trends of financial (dis)soundness can be recognized as part of the supplier evaluation as well as part of the internal ratings by banks. It follows that hypothesis can be identified which in future work can be empirically tested. The result also provides a start to initiate further research e.g. about a possible (partial) externalization of already existing internal rating data by credit institutions. This then could be used in the context of supplier evaluation reducing overall cost.
Keywords: G00; G21; G18; 330; access to finance; SMEs; supplier evaluation; quality; market